Pertumbuhan dan Produksi Bawang Merah (Allium ascalonicum L.) pada Berbagai Jarak Tanam dan Dosis Pupuk NPKMg: Growth and Production of Shallot (Allium ascalonicum L.) at Various Planting Space and Fertilizers Dose of NPKMg (Jurnal Hortikultura Indonesia, 2024)
Shallot (Allium ascalonicum L.) is a strategic commodity in Indonesia. The needs of shallots increase continuously, so production should be increased. Factors determining production include planting space and fertilization. This research aims to determine the appropriate planting space and NPKMg fertilizer dose for shallot plants. The experiment was arranged factorially in a Randomized Complete Group Design with three replications using the SS-Sakato variety. The first factor is planting space, namely 10 cm x 10 cm, 10 cm x 15 cm, 15 cm x 15 cm, and 15 cm x 20 cm. The second factor is the dose of NPKMg fertilizer (10:12:17:2), namely 200, 400, 600, and 800 kg ha-1. Planting space of 10 cm x 15 cm produces higher leaf area, number of tubers and fresh weight per hill, tile yield, and productivity compared to planting space of 10 cm x 10 cm, 15 cm x 15 cm, and 15 cm x 20 cm. The highest transpiration rate was also produced from 10 cm x 15 cm for all NPKMg fertilizer doses (10:12:17:2), except 400 kg ha-1. Increasing the fertilizer dose of 200 - 800 kg of NPKMg (10:12:17:2) did not increase tuber growth and yield because the N content is low (20 - 80 kg ha-1), so additional single N source fertilizer is needed.Keywords: tuber weight, number of tubers, NPKMg, SS-Sakato